Raising Public Awareness in Preserving Historical Heritage Sites Of Patah Sembilan Stone in Langkah Serentak Limbai Seayun Land - Purnama, Boby Yasman; Wulandari, Dea Nanda; Rose, Julia (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
This journal aims to examine the historical events or relics that developed in the Senamat Ulu Village, Bathin III Ulu Sub-district, Muaro Bungo Regency, Jambi Province. This article uses historical methods by library research, including archival studies, observations and interviews with related sources. Departing. From the history, uses with make sense and conscience things to know the history around us, the existence of the Batu Patah Sembilan historical become the tools to tell the importance of the presence of this site in the birth of civilization on Earth "Langkah Serentak Limbai Seayun". With the preservation of the existing historical sites, it will be able to provide many benefits to various aspects of people's lives in the Ulu Senate as well as identification of that village. A historical relic from the Great Stone Age (Megalithic) to this day can still be able to know by its history and existence, and also about the historical stories that have developed in the civilization of society from generation to generation.